O interesse acadêmico pela educação física escolar em um curso de licenciatura: uma análise documental - Amorim, Bruna Karolaynne Martins (Universidade Federal do Tocantins, 2023)
The objective of the present study is to map which themes are addressed in the final graduation works in a Physical Education course with a Licentiate qualification. This is a documental research, of a historical and primary nature, whose sample consisted of a total of 26 Course Completion Works of the Federal University of Tocantins (UFT), prepared by the first two groups of newcomers of the Degree in Education Physics in 2015. The results were organized from three specific sub-areas, namely: Biodynamics; Sociocultural; and pedagogical. It appears that, in the universe of the 26 works analyzed, ten were focused on Biodynamics, whose target audience was mostly constituted by the Elderly. In the Sociocultural themes, six works were explained, and we identified a total of ten works, whose respective objects of study were directed to School Education. In view of the proposed objective through the analysis of the course conclusion works, it was concluded that most of the monographs used the school space as a locus of research, although some have moved away almost entirely from the pedagogical theme.